The short term visual, refractive and Topographic outcome of Corneal Collagen Crosslinking in Keratoconus - Kaliaperumal, Renuga Devi; Purushothaman, Amudha; Krishnan, Thiruvengada; Shivananda (Asian Journal of Medical Sciences, 2021)
Background: Keratoconus is a condition characterized by biomechanical instability of cornea presenting in a progressive asymmetry and bilateral way. Corneal collagen cross-linking with riboflavin and UVA is a technique that has influenced the treatment of Keratoconus by arresting the progression. Aims and Objectives: The aim of the study was to assess the short-term efficacy and safety of collagen cross-linking in Keratoconus. Materials and Methods: This prospective, nonrandomized, interventional case study was conducted at Aravind Eye hospital and PGI, Puducherry from June 2012 to April 2013. Statistical analysis was done using repeated measures ANOVA and Bonferonn’s using IBM SPSS Inc. 20.Version. Results: A total of 30 patients were enrolled in this study and standard cross linking procedure was done. It was found that UCVA, BSCVA both improved about 40%. Spherical Equivalent reduced by 0.7 D, cylinder reduced by 0.8 D and total astigmatism decreased by about 0.4 D. Steepest K value reduced by 2 D, Irregularity and astigmatism at 3 and 5 mm also changed significantly (P<0.05). Conclusion: Collagen cross-linking arrests the progression of Keratoconus. It seems to improve the UCVA and BCVA and it is a safe and effective procedure.